Answer:
x = 4
Step-by-step explanation:
First u need to distribute the -1 to (x + 4), creating the equation, -8 = -x - 4. Then add the -4 to both sides, and you get, -4 = -x. Then divide by -1 to both sides, and x = 4.
Question- The image is appearing blank for me, could you try and re-send it or forward it to me. Thank you.
Answer:
A. 7
Step-by-step explanation:
z ÷ (–7) = –1.
multiply each side by -7
z ÷ (–7)*-7 = –1.*-7
z = 7
Answer:
a y = 2
b.y = 14
c. y =56
Step-by-step explanation:
a .6 (1)- 4=2
y=2
b. 6 (3)- 4
=18-4
y=14
c. 6 (10) - 4
= 60 - 4 =56